A pharmaceutical hydrogen-bonded covalent organic polymer for enrichment of volatile iodine. Issue 86 (27th November 2017) - Lin, Lin; Guan, Heda; Zou, Donglei; Dong, Zhaojun; Liu, Zhi; Xu, Feifan; Xie, Zhigang; Li, Yangxue
Abstract : A pharmaceutical hydrogen-bonded covalent organic polymer (pha-HC OP-1) is constructed with the formation of two types of bonds using the pharmaceutical isoniazid as a bifunctional linker. The as-synthesised pha-HC OP-1 exhibits good adsorption ability for iodine molecules. Abstract : Porous organic polymers (POPs) are emerging porous materials for various applications. So far, POPs are currently synthesised by a few limited synthetic chemical reactions, leading to a lack of new structures and properties. Thus, expanding structural diversity is highly desired for the development of this promising class of porous materials. Herein, adopting pharmaceutical isoniazid as a difunctional linker, a pharmaceutical hydrogen-bonded covalent organic polymer (pha-HC OP-1) has been synthesised for iodine enrichment. The structure and morphology are studied by TGA, FT-IR, FE-SEM, HR-TEM and 13 C CP/MAS NMR. Powder X-ray diffraction and N2 adsorption–desorption analysis show that pha-HC OP-1 is amorphous and porous with a surface area of 217.31 m 2 g −1 . The pha-HC OPs are spherical particles with an average size of 20 nm. Due to the abundant porosity, π-conjugated phenyl rings, as well as functional –CO–NH– building units, pha-HC OP-1 exhibits a good adsorption ability for iodine molecules. The pha-HC OP-1 has a high uptake value of 131 wt% via vapor trapping adsorption. Meanwhile, pha-HC OP-1 also exhibits an outstanding iodine adsorption in solution, and the maximum adsorption capacity reaches as high as 833.33 mg g −1 analyzed using a Langmuir model. In addition, the thermodynamic parameters Δ G, Δ H and Δ S indicate that the adsorption of iodine by pha-HC OP-1 is feasible, spontaneous and endothermic. pha-HC OP-1 represents an elegant example of using pharmaceutical molecules as building blocks to construct porous POPs for reversible adsorption of radioactive iodine.